Role of spectral doppler in the differentiation of benign and malignant cervical lymphadenopathy - Mohmed Imran Wagay; Fayaz Ahmad Wagay; Shazia Qadir; GH Mohammad Wani (Al Ameen Medical College, 2014)
Introduction: Differentiating benign from malignant lymphadenopathy is often a diagnostic challenge to medical professionals and multiple non invasive modalities from palpation to MRI have been used. Histopathology remains the gold standard but imaging modalities are frequently used. The main objective of our study is to assess the accuracy of spectral Doppler in differentiating benign and malignant lymphadenopathy. Methods: A prospective study was done in patients with cervical nodes and the Doppler study was done primarily assessing the spectral doppler features and the diagnosis was compared with histopathology. Results: Reactive nodes usually showed hilar vascularity. Metastatic nodes showed Peripheral and chaotic multifocal vascular signals. Resistive Index and Pulsatility Index were the most important markers among the spectral parameters for the differentiation of benign and malignant lymphadenopathy. RI and PI of malignant nodes was significantly higher than benign nodes. PSV of the nodes was not much different but EDV was low in metastatic nodes. EDV> 11.1 cm/s has 100% negative predictive value for nodal metastasis, and EDV<3.4 cm/s has 100% specificity and PPV for metastasis. Tubercular nodes shows indeterminate doppler characteristics. Conclusion: Colour doppler sonography is a highly efficacious investigation for differentiation of benign and malignant lymphadenopathy Colour doppler can be used to prevent unnecessary invasive biopsy in many patients particularly in those patients where we get very low values of RI and PI and very high values for EDV. RI is the single most important parameter in the differentiation of benign and malignant lymphadenopathy. Cut off value of 0.7 for RI and 1.3 for PI, yield acceptable sensitivity, specificity and accuracy.